2020
DOI: 10.22271/chemi.2020.v8.i5l.10401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea briquettes deep placement on yield and nitrogen use efficiency of rice

Abstract: Effect of urea briquette deep placement with applicator on yield and yield attributing parameters of rice studied and experiment was conducted at "Research cum Instructional farm", "Indira Gandhi Krishi Vishwavidhyalaya", Raipur (C.G.) during kharif-2019 in randomized block deign with ten treatments and three replication with rice variety "IGKV-R1" used as test crop.The treatment consists of different level of nitrogen combine with different mode of urea application, i.e. T1 (control), T2 (N0), T3 (100 kg N ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Kadam et al (2001) found that the placement of urea briquette enhances grain yield of rice over split application of urea and the additional yield varied from 0.23 to 1.48 t ha -1 . The deep placed Urea-DAP briquette increased grain yield of rice from 11 to 86% and gross yield 9 to 62% prilled urea (Deep, Bachkaiya, Tedia, & Verma, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Kadam et al (2001) found that the placement of urea briquette enhances grain yield of rice over split application of urea and the additional yield varied from 0.23 to 1.48 t ha -1 . The deep placed Urea-DAP briquette increased grain yield of rice from 11 to 86% and gross yield 9 to 62% prilled urea (Deep, Bachkaiya, Tedia, & Verma, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Manual deep placement of Urea Briquettes (UB) has been shown to enhance yields by (15.0-20.0%) and improve the agronomic effectiveness of NUE by (50.0-70.0)% (Bulbule et al, 1996). This technique has also substantially increased rice grain yields from (11.0-86.0%) (Deep et al, 2020). The GS employs the evaluation of the Normalized Difference Vegetation Index (NDVI), which relies on the reflection of light in the red and near-infrared regions.…”
Section: Introductionmentioning
confidence: 99%